SARS-CoV-2 presented in the air of an intensive care unit (ICU). (February 2021) - Jin, Tingxu; Li, Jun; Yang, Jun; Li, Jiawei; Hong, Feng; Long, Hai; Deng, Qihong; Qin, Yong; Jiang, Jiajun; Zhou, Xuan; Song, Qian; Pan, Chunliu; et al.
Highlights: SARS-CoV-2 virus was present in the air in the ICU. Virus may be discharged in aerosol for days after patients test negative. The finding may be one of the reasons for patients` re-detectable positive. The clinical guidelines for recovered COVID-19 patients need to be improved. Abstract: As coronavirus disease 2019 (COVID-19) is spreading worldwide, there have been arguments regarding the aerosol transmission of its causative agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Moreover, some re-detectable positive (RP) patients have been reported. However, little attention has been given to the follow-up of recovered patients, and there is no environmental evidence to determine whether these patients continue to shed the virus after they test negative. Therefore, with an objective to test the hypothesis of airborne transmission of SARS-CoV-2, it is necessary to 1) determine whether SARS-CoV-2 particles are present in the indoor air and 2) determine whether recovered patients are still shedding virus, thus providing much-needed environmental evidence for the management of COVID-19 patients during the recovery period. In this study, surface and air samples were collected from an intensive care unit (ICU) containing one ready-for-discharge patient. All surface samples tested negative, but the air samples tested positive for SARS-CoV-2. This implies that SARS-CoV-2 particles may be shed in aerosol form for days after patients test negative. This finding may be one of the reasons for the observation of RP patients; therefore, there is a need for improved clinical and disease management guidelines for recovered COVID-19 patients.